Investigation of Off-shore Wind Energy Potential in Türkiye: A Case Study of Bandırma Bay (Aintelia Science Notes, 2022)
In this study, the main factors in off-shore wind energy have examined and the current situation in the world and in Türkiye has presented. In addition, the pre-investment feasibility analysis for the planned offshore wind power plant facility in Türkiye and the steps to be followed have examined in detail. According to these plans, a case study has conducted for Bandırma Bay, which has high offshore wind energy potential. Hourly wind speed and direction data of the Bandırma Meteorological Station of the Meteorological Service between 2010 and 2020 were obtained. The analyzes carried out showed that the wind efficiency of the region is suitable for off-shore wind power plant installation. In addition, the most suitable location for the installation of the offshore wind power plant in Bandırma has been proposed.
Keywords: Off-shore wind energy; off-shore installations; wind power plants